Cloning of a novel rice TE and its structural comparison with CACTA elements - TIAN Ping-fang; WANG Guo-dong; LI Qun; LI De-bao; HE Zu-hua (浙江大学学报. 农业与生命科学版, 2004)
The genomic structure of the previously reported Rim 2 element induced by rice blast pathogen Magnaporthe grisea was studied. By using a Rim 2 cDNA probe to screen and subsequently subclone the Rim 2 bacterial artificial chromosome, a genomic clone Rim 2-569 was obtained. Sequence analysis revealed that Rim 2-569 possesses the fundamental structure of Class 2 transposable elements, with perfect terminal inverted repeats in both ends, direct and inverted sub-terminal repeats, along with 3 bp target site duplication. The sequence ‘CACTG’ in the terminal inverted repeats distinguishes it from reported CACTA elements. The element has a open reading frame encoding a putative transposase that shares low similarity with TNP2, TNPD and other putative transposases of CACTA elements. No open reading frame encoding TNP1/TNPA-like DNA binding protein were found in this element. Southern hybridization showed the ubiquitous distribution of Rim 2 elements in rice varieties of different origins, along with data mining, indicating plentiful copies of the element family. These features attest this Rim 2 element belonging to a novel transposon family different from the reported CACTA elements.